Reconstruction of the Standards for Assessing the Probative Value of Electronic Evidence in the Indonesian Criminal Justice System: A Cyberlaw Perspective - Adrian Bima Putra (CV Edujavare Publishing, 2026)
The rapid development of information technology has transformed the evidentiary system within Indonesia's criminal justice process. Although electronic information and electronic documents have been recognized as legal evidence under Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions, there remains no comprehensive legal standard governing the assessment of their evidentiary value. This condition has created legal uncertainty regarding authenticity, integrity, reliability of electronic systems, chain of custody, and digital forensic verification. This research aims to analyze the legal framework governing electronic evidence in Indonesia and to formulate a reconstruction model for assessing the evidentiary strength of electronic evidence from a cyber law perspective. The study employs normative legal research using statutory, conceptual, and case approaches. Legal materials are analyzed qualitatively through descriptive-analytical methods. The findings reveal that the current legal framework remains fragmented and lacks comprehensive standards for evaluating electronic evidence. Consequently, this study proposes a reconstruction model consisting of five principal indicators: authenticity, integrity, reliability of electronic systems, chain of custody, and digital forensic verification. This model is expected to serve as a conceptual basis for reforming Indonesia's criminal procedural law in order to enhance legal certainty, justice, and the effectiveness of evidence assessment in technology-based criminal cases.